Comparison of Post-Operative Results of Early Versus Delayed Open Reduction and Internal Fixation of Isolated Mandibular Fractures - Hassan, Amna; Shafqat, Yumna; Babar, Adnan; Mahmood, Saad; Muzaffar, Amna; Afzal, Muhammad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the impact of treatment time of open reduction internal fixation of mandibular fractures in post-operative complications.Study Design: Quasi-experimental study.Place and Duration of Study: Oral and Maxillofacial Surgery, Armed Forces Institute of Dentistry, Combined Military Hospital, Rawalpindi Pakistan, from Jan to Jun 2019.Methodology: A hundred and four patients with isolated mandibular fractures diagnosed clinically and radiologically were included in the study. Group-I was the early Group consisting of cases reported under 72 hours, and Group-II was the delayed Group consisting of patients after 72 hours and within fourteen days. Treatment outcomes were assessed and compared for all patients based on clinical parameters in the post-operative period during follow-up.Results: One hundred and four patients with mandibular fractures were treated with open reduction internal fixation. On a periodic follow-up of 6 months, all patients were evaluated for malocclusion, surgical site infection, hardware exposure, and non-union complications. Group-I showed six patients (11.70%) with malocclusion, whereas three patients (6.10%) in Group-II had malocclusion (p-value=0.295). Surgical site infection was present in 2(3.84%) patients in Group-I and 3(5.76%) patients in Group-II (p-value=0.647). There was no case of non-union and three patients (5.76%) of hardware exposure in Group-I and two patients (3.84%) in Group-II (p-value=0.647). No statistically significant increase in post-operative complications in malocclusion, surgical site infection, hardware exposure, and non-union was found in Group-II with comparison Group-I.Conclusion: Delay in the surgical intervention of mandible fractures does not lead to increased post-operative complications.